Segment power analysis of collegiate softball hitting - Bordelon, N. M.; Wasserberger, K. W.; Downs Talmage, J. L.; Friesen, K. B.; Washington, J. K.; Oliver, G. D. (Sports Biomechanics, 2021)
The primary aim of this investigation was to describe the energy flow through the kinetic chain during softball hitting using a segmental power analysis. Twenty-three NCAA Division I collegiate softball athletes (20.4 ± 1.7 yr; 166.7 ± 22.0 cm; 74.9 ± 15.9 kg) performed three maximum effort swings off a stationary tee placed in the middle of the strike zone. Pelvis, trunk, humerus, forearm and hand segment powers were integrated across four phases of the softball swing (load, stride, acceleration, and follow-through). The load and stride phases had low segment energy inflow and outflow values as well as net segment energy flow for all body segments compared to subsequent phases of the swing. The acceleration phase showed large trunk inflow values relative to the pelvis. There was also descriptively larger front compared to back-side upper extremity inflow. Finally, the follow-through phase showed primarily energy outflow for the upper extremity segments likely attributed to slowing down rotation.